Helmet use and associated factors among thai motorcyclists during Songkran festival - Siviroj P. (2017)
The aim of this study was to assess helmet use and associated factors among motorcycle riders during Songkran festival in Thailand. A cross-sectional survey was conducted to determine the prevalence of helmet use among Thai motorcycle riders (sample size = 18,998) during four days of the Songkran festival. For this sample, the population of motorcycle riders was consecutively selected using quota sampling from 12 petrol stations in four provinces from each of the four main geographical regions of Thailand. The study was conducted at petrol stations at roads in town, outside town and highway at different time intervals when trained field staff administered a structured questionnaire and performed an observation checklist. Results indicate that 44.2% of the motorcycle riders and 72.5% of the motorcycle passengers had not been using a helmet. In multivariable analysis demographics, environmental factors, helmet use experiences and attitudes and recalling a lower exposure to road safety awareness (RSA) campaign were associated with non-helmet use among motorcyclists. It appears that the RSA campaign may have some positive effect on reducing non-helmet use among motorcycle riders during the Songkran festival. © 2012 by the authors; licensee MDPI, Basel, Switzerland.